Análise fluidodinâmica computacional de winglets - Kuroda, Rodrigo Kenji Rodrigues (2022)
A winglet is a device used on the wingtips to improve the aerodynamic efficiency of the aircraft by decreasing the induced drag and, therefore, reduce the vortices. In this work, it will be modeled and analyzed two different types of winglets - blended and split – with different cant angles and different angles of attack. The modeling part of the work will be done using a CAD software to draw the winglets into the wing tip. After modeling, the wings will be imported into the Computational Fluid Dynamics software - in this case, ANSYS Fluent – to simulate the drag and lift coefficients, and verify the intensity of the vortices formed. These simulations will be compared with each other – blended versus split - and they will also be compared with a winglet-free wing that will be the experimental control.